Measurement of customer satisfaction in online banking services in Melli Bank of Iran - Nikou, Seyed Hossein; Harihodin Selamat, Assoc. Prof. Dr.; Faculty of Advanced Informatics School (2012)
Thesis (Sarjana Sains (Pengurusan Teknologi Maklumat)) - Universiti Teknologi Malaysia, 2012